015 Reduced risk of secondary progressive multiple sclerosis by treatment with clad- ribine tablets: CLARITY study analysis. Issue 6 (27th May 2022) - Vermersch, Patrick; Giovannoni, Gavin; Soelberg-Sorensen, Per; Rammohan, Kottil; Cook, Stuart; Keller, Birgit; Roy, Sanjeev
Abstract : Background: Cladribine tablets 10mg, cumulative dose 3.5mg/kg (CT3.5) over 2 years, showed efficacy vs placebo in patients with relapsing multiple sclerosis. This post-hoc analysis explored the relationship between baseline Expanded Disability Status Scale (EDSS) and risk of progression to secondary progres- sive (SPMS, EDSS ≥6.0) in CLARITY. Methods: This analysis used a proxy composite definition of SPMS. Patients progressing to EDSS ≥6.0 were defined as ≥1 post-baseline EDSS ≥6.0 with 3- or 6-month confirmed disability progression (CDP). Results: Proxy SPMS progression was lower for CT3.5 vs placebo: overall (6.7% vs 13.5% [OR 0.46; 95%CI: 0.28–0.76]; P=0.0024); baseline EDSS ≤3.0 subgroup (3.5% vs 7.7% [OR 0.44; 95%CI: 0.19–0.99]; P=0.047]); baseline EDSS ≥3.5 subgroup (12.2% vs 22.4% [OR 0.48; 95%CI: 0.26–0.9]; P=0.0212). Patients with 3-month CDP with EDSS ≥6.0: 3.5% vs 8.0% (OR 0.42 [95%CI: 0.22–0.82]; P=0.0114); 6-month CDP with EDSS ≥6.0: 2.8% vs 5.8% (OR 0.48 [95%CI: 0.22–1.02]; P=0.0566). Conclusions: Risk of progressing to proxy SPMS within 2 years of treatment or experiencing EDSS ≥6.0 was sig- nificantly reduced with CT3.5 compared to placebo, regardless of baseline EDSS. CLARITY: NCT00213135 g.giovannoni@qmul.ac.uk